Effect of oral metronomic chemotherapy on quality of life in advanced or metastatic head and neck cancers - Sharma, Manish Kumar; Ramkumar, B.; Raja, G.; J. G., Atul; Parai, Shaoni; Rooban, N. Vasanth (International Journal of Research in Medical Sciences, 2024)
Background: Oral Metronomic chemotherapy (OMCT) is an emerging therapeutic option in advanced/metastatic, head and neck squamous cell carcinoma (HNSCC). It is ideal for frail patients not candidates for platinum-based chemotherapy, and who have minimal response with progressive worsening of quality of life (QOL). To assess the effect of OMCT on changes in quality of life (QOL) in advanced/recurrent HNSCC patients. Methods: Patients with advanced/metastatic recurrent HNSCC, not amenable to radical therapy were included in the study. QOL was assessed with the European organization for research and treatment of cancer (EORTC) QLQ-C30 and QLQ-H&N 35 questionnaires at enrollment and at regular follow up intervals after starting MC. Results: Out of 54 patients, 50 % patients had grade 3 or more pain at enrolment, which improved after OMCT with only 5 % having grade 3 or more pain at 6 months. Mean QLQ-C 30 score at the time of presentation was 68.4. With oral MC, there was a steady increase in QOL score QLQ-C30; 75.35 at 2 months, 81.26 at 4 months, and 85.38 at the end of 6 months. Mean QLQ-H and N 35 score at the time of presentation was 62.50, which gradually improved with oral MC; 71.16 at 2 months, 75.43 at 4 months, and 80.69 at the end of 6 months. Conclusions: The use of oral metronomic therapy with methotrexate, gefitinib and celecoxib significantly improved the QOL and pain control in patients with advanced/recurrent HNSCC.